Principal Leadership Strategies to Improve Student Achievement: A Case Study of MI Darul Ulum Semarang - Hermawati, Fetty; Nurkolis; Egar, Ngasbun (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the principal’s management strategies in improving student achievement at MI Darul Ulum, Ngaliyan District, Semarang City. Student achievement is an important indicator of the success of educational institutions in achieving educational goals. In this context, the school principal plays a strategic role in formulating policies, managing school resources, and creating a conducive learning environment for students. This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, teachers, the school committee, parents, and students as research informants. Data analysis was conducted using an interactive model consisting of data condensation, data display, and conclusion drawing. The validity of the data was ensured through source triangulation, technique triangulation, and time triangulation. The results show that the principal’s management strategies in improving student achievement are implemented through three main stages: strategy formulation, strategy implementation, and strategy control. In the formulation stage, the principal conducts a school needs analysis and formulates programs to improve student achievement through participatory planning involving various stakeholders. In the implementation stage, the school carries out academic and non-academic programs such as additional tutoring, remedial learning, enrichment activities, and extracurricular programs to develop students’ potential. In the control stage, the principal conducts monitoring, evaluation, and follow-up actions to ensure the effectiveness of educational programs. The findings indicate that systematic, collaborative, and sustainable management strategies implemented by the principal can improve both academic and non-academic student achievement. These findings are expected to provide insights for educational institutions in developing effective school management strategies to enhance student achievement.